2020
DOI: 10.3390/ijerph17072232
|View full text |Cite
|
Sign up to set email alerts
|

Demoralization and Its Relationship with Depression and Hopelessness in Suicidal Patients Attending an Emergency Department

Abstract: Emergency departments (EDs) play an increasingly crucial role in the management of patients with suicidal behavior (SB). Demoralization has been associated with SB in various populations and conditions, but little is known about the effect of this construct in SB patients who attend an ED. Therefore, a more inclusive SB assessment which considers the demoralization construct could be useful in clinical practice. The main aim of this study was to assess the presence and severity of demoralization in patients vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 58 publications
0
41
2
Order By: Relevance
“…P a r t i c i p a n t s a n s w e r e d i n q u i r i e s r e g a r d i n g t h e i r sociodemographic situations as well as a series of questionnaires, some administered by the psychiatrist in charge of the study inclusion and some self-reported. Other aspects of this global project on suicide, not relevant to the present study, have resulted in five publications (28)(29)(30)(31)(32). This study was approved by the local Research Ethics Committee under the registration number 14-168.…”
Section: Methodsmentioning
confidence: 99%
“…P a r t i c i p a n t s a n s w e r e d i n q u i r i e s r e g a r d i n g t h e i r sociodemographic situations as well as a series of questionnaires, some administered by the psychiatrist in charge of the study inclusion and some self-reported. Other aspects of this global project on suicide, not relevant to the present study, have resulted in five publications (28)(29)(30)(31)(32). This study was approved by the local Research Ethics Committee under the registration number 14-168.…”
Section: Methodsmentioning
confidence: 99%
“…And does this type of reasonableness lead to a certain resistance, resulting in the generalization of this population and banalization of the suicidal risk? Most of the data and reflections reported so far may indicate a highly deterministic conceptualization of the evolution of certain neurological diseases, in which the patient and his clinician may feel impotent and imprisoned [ 52 ]. Could one think that having SI is a way for the patient, on the contrary, to control what little he can do?…”
Section: Reflections Regarding Suicidality In Neurological Diseases Amentioning
confidence: 99%
“…After its introduction into the psychiatric literature [81], MiL was recently described as one's perception of their own coherence, purpose, and significance [82] while demoralization was defined "a persistent failure to cope with stresses" [83], of which constitutive components are loss of MiL, hopelessness or disheartenment, helplessness, sense of failure, and dysphoria [84,85]. These two constructs are intimately and opposingly connected and have been investigated in our institutions among suicidal individuals who were confronted with extreme life situations that have led to an often-incomprehensible fracture between a "before" and an "after" living experience [84][85][86][87][88][89][90][91][92][93]. In the context of CTE in contact sports, retired athletes experience profound changes in their lives, worsening the outlook and the quality of their living condition.…”
Section: Psychiatric and Psychosocial Hypotheses For Suicidality Etiomentioning
confidence: 99%
“…The majority of the studies have suggested that demoralization is distinguishable from depression [84,85,92]. However, in patients with cancer [94][95][96][97][98][99][100], Parkinson's disease [101], as well as other psychiatric and medical conditions [89,[102][103][104][105], there may be frequent overlaps between demoralization and depression. Nevertheless, demoralization can occur independently of depression and the two conditions are not necessarily linked by a hierarchical connection [89,99,105,106].…”
Section: Psychiatric and Psychosocial Hypotheses For Suicidality Etiomentioning
confidence: 99%